Acemannan induces rapid early osseous defect healing after apical surgery: A 12-month follow-up of a randomized controlled trial - Cuong Le Van; Hien Pham Thi Thu; Polkit Sangvanich; Vannaporn Chuenchompoonut; Pasutha Thunyakitpisal (Elsevier, 2020)
Background/purpose: Acemannan is an osteoinductive material. This study's objective was to compare the outcomes of bone defect healing using 3-dimensional images after apical surgery with or without adding acemannan sponges. Materials and methods: Twenty-two anterior teeth from 9 males and 13 females requiring apical surgery were included in this randomized controlled trial. Post-surgery, the bone defects were randomly divided into three groups: blood clot control, 5-, or 10-mg acemannan sponge groups. CBCT scans were taken immediately (baseline), 3-, 6-, and 12-month post-surgery. Sagittal serial sections (1 mm thick slices parallel to the long axis of the tooth) of the defect image were created. The defect boundary was located and the total bone defect volume (BDV) was calculated from the sum of the volume of the serial defect sections. The bone healing was assessed by the percentage of total bone defect volume reduction (%ΔBDV). The paired t-test and one-way ANOVA were used to analyze the differences within each group and between groups, respectively. Results: The baseline mean BDV of the control, 5-, and 10-mg acemannan groups were not significantly different (p > 0.05). After treatment, the mean BDV for each group was reduced in a time-dependent manner. Compared with the control group, the 5- and 10-mg acemannan groups had a significantly greater %ΔBDV (approximately 2- and 1.89-fold) at 3-months post-surgery, respectively (p < 0.05). However, at the 6- and 12- month follow-up, the %ΔBDV was not significantly different between the groups. Conclusion: These data suggest acemannan enhanced early bone healing after apical surgery.